THE SIGNIFICANCE OF ENHANCING LANGUAGE PROFICIENCY IN PHILOLOGY STUDENTS - Khajiyeva Mukhlisa Saidjon qizi (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the critical importance of improving linguistic competence among students pursuing philology. It delves into the multifaceted benefits of language proficiency in the field of philology, highlighting its role in understanding cultures, literature, historical texts, and linguistic nuances. The article emphasizes the practical and theoretical aspects of linguistic competence and its impact on the academic and professional development of philology students.